Role of Nutrient-Enriched Biochar as a Soil Amendment during Maize Growth: Exploring Practical Alternatives to Recycle Agricultural Residuals and to Reduce Chemical Fertilizer Demand - Kizito, Simon; Luo, Hongzhen; Lu, Jiaxin; Bah, Hamidou; Dong, Renjie; Wu, Shubiao (Sustainability, 2019)
Recycling and value-added utilization of agricultural residues through combining technologies such as anaerobic digestion and pyrolysis could double the recoverable energy, close the nutrient recycle loop, and ensure cleaner agricultural production. This study assessed the beneficial application of biochar to soil to recycle digestate nutrients, improve soil quality, and reduce conventional chemical fertilizer. The addition of digestate-enriched biochar improved soil quality as it provided higher soil organic matter (232%–514%) and macronutrients (110%–230%) as opposed to the unenriched biochar and control treatments. Maize grown in soil amended with digestate-enriched biochar showed a significantly higher biomass yield compared to the control and non-enriched biochar treatments but was slightly lower than yields from chemical fertilizer treatments. The slightly lower yield (20%–25%) achieved from digestate-enriched biochar was attributed to slower mineralization and release of the adsorbed nutrients in the short term. However, digestate-enriched biochar could in the long term become more beneficial in sustaining soil fertility through maintaining high soil organic matter and the gradual release of micronutrients compared to conventional chemical fertilizer. Positive e ects on soil micronutrients, macronutrients, organic matter, and biomass yield indicates that enriched biochar could partly replace chemical fertilizers and promote organic farming in a circular economy concept.
Keywords: Agricultural residues; Anaerobic digestate; Nutrient recycle; Agroecosystems; Corn fertilization